PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KOMITMEN ORGANIZATIONAL TERHADAP KINERJA - Sutaat, 05.2502.0014; Yunianto, Askar (Students Journal of Economic and Management, 2012)
This study aims to analyze (1). Transfomasional leadership influence on faculty performance (2). Influence the motivation of faculty performance (3). Organizational commitment to faculty performance partially or jointly. The research was conducted at the State Islamic Institute (IAIN) Walisongo Semarang sample of 100 respondents. By using purposive sampling method with a minimum education level criteria are postgraduate (S2) and a 3-year tenure. The results of this study indicate that (1). Transformational leadership has a significant influence on the performance of lecturers with t count equal to 2.633 (2). Work motivation has significant influence on the performance of lecturers with t count equal to 2.933 (3). Organizational commitment have a significant influence on the performance of lecturers with t count of 2.532. Taken together transformational leadership, motivation, and organizational commitment have a significant influence on the performance of lecturers with F count of 26.573. Thus transformational leadership, motivation, and organizational commitment should always be considered for performance enhancement Lecturer State Islamic Institute (IAIN) Walisongo Semarang.Key words: Transformational Leadership, Work Motivation, Organizational Commitment, Employee.